1989
DOI: 10.1002/cne.902850306
|View full text |Cite
|
Sign up to set email alerts
|

Retinotopic organization within the lateral posterior complex of the cat

Abstract: Electrophysiological mapping methods were employed to systematically study the retinotopic organization within the cat's lateral posterior complex (LP). Visual responses were recorded in all the major subdivisions of the LP as well as in several adjoining cell groups. Specifically, separate representations of the visual field were identified for pulvinar, zones LP1-c, LP1-r, LPi, and LPm. Partial representations of the visual field were also evident in the geniculate wing, subdivisions of the lateral posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 69 publications
12
56
1
Order By: Relevance
“…6). Although the number of our recording sites in LP1-c is limited (10 in 11 cats), the proposed division perfectly matches the diverse morphology and connectivity of these subregions (Berson and Graybiel, 1978;Updyke, 1983;Abramson and Chalupa, 1988;Garey et al, 1991;Kelly et al, 2003;Huppe-Gourgues et al, 2006) and differences of their neuronal responses in anesthetized cats (Casanova et al, 1989;Chalupa and Abramson, 1989;Hutchins and Updyke, 1989;Dumbrava et al, 2001). There is, however, a discrepancy between our data and those of others with regard to the extent of the dorsolateral region bordering on the pulvinar.…”
Section: Lp-p Recording Sitessupporting
confidence: 69%
See 1 more Smart Citation
“…6). Although the number of our recording sites in LP1-c is limited (10 in 11 cats), the proposed division perfectly matches the diverse morphology and connectivity of these subregions (Berson and Graybiel, 1978;Updyke, 1983;Abramson and Chalupa, 1988;Garey et al, 1991;Kelly et al, 2003;Huppe-Gourgues et al, 2006) and differences of their neuronal responses in anesthetized cats (Casanova et al, 1989;Chalupa and Abramson, 1989;Hutchins and Updyke, 1989;Dumbrava et al, 2001). There is, however, a discrepancy between our data and those of others with regard to the extent of the dorsolateral region bordering on the pulvinar.…”
Section: Lp-p Recording Sitessupporting
confidence: 69%
“…In two animals, every third section was stained to reveal acetylcholinesterase activity to better distinguish the three major zones in LP-P (Berson and Graybiel, 1983). The physiologically estimated retinotopic positions corresponding to recording sites were finally verified from postmortem anatomical analysis with reference to the maps provided by Hutchins and Updyke (1989) for LP-P and Tusa et al (1981) for visual cortical areas. The retinotopy of the MSS recording sites was not confirmed physiologically, and we therefore relied only on the histology matched to the maps defined by others (Tusa et al, 1981;Grant and Shipp, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological recording studies have also found that neurons in SG and LP have similar properties. Both have large receptive fields and respond very reliably to fast moving visual stimuli (Hicks et al, 1984;Hutchins and Updyke, 1989;Casanova and Molotchnikoff, 1990). Furthermore, the present data show that the dorsal SG provides projections to the PR and the L, as does the adjacent LP.…”
Section: Direct and Indirect Visual Thalamo-amygdala Connectivitysupporting
confidence: 64%
“…In addition, we suggest that the caudal pole of PoM in cats may be akin to anterior portions of the suprageniculate nucleus of monkeys: both occupy a similar location, are major targets for ascending spinothalamic and spinal trigeminal inputs (Poggio and Mountcastle, 1960;Berkley, 1983;Burton and Craig, 1983;Ralston and Ralston, 1992), and project to the granular insular cortex and adjacent somatosensory fields (Burton and Kopf, 1984;Mufson and Mesulam, 1984;present results). In contrast, the nucleus usually referred to as Sg in cats is continuous with the lateral posterior complex (Graybiel and Berson, 1980;Bowman and Olson, 1988;Rodrigo-Angulo and Reinoso-Suá rez, 1995) and the dorsal division of the medial geniculate (Winer, 1992), and is basically involved in auditory and visual processing (Calford, 1983;Hicks et al, 1984;Norita and Katoh, 1987;Hutchins and Updyke, 1989). Thalamic connectivity, therefore, argues for a basic similarity between areas DI and GI of cats and the dysgranular and granular insular fields of macaques.…”
Section: The ''Insular'' Areas: Comparative Considerationsmentioning
confidence: 78%
“…Studies have shown that both LM and Sg receive ascending inputs from the pretectal nuclei and deep strata of the superior colliculi (Graybiel and Berson, 1980;Reinoso-Suá rez, 1982, 1995;Norita and Katoh, 1987), and contain visually responsive neurons that display large receptive fields with a rough retinotopic arrangement (Hicks et al, 1984;Hutchins and Updyke, 1989). In addition to visual input, Sg receives input from brainstem auditory nuclei.…”
Section: Thalamic Connections: Organization and Functional Implicationsmentioning
confidence: 98%